2007
DOI: 10.1093/toxsci/kfm110
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic Acid Induced Developmental Toxicity in the Mouse is Dependent on Expression of Peroxisome Proliferator Activated Receptor-alpha

Abstract: Perfluorooctanoic acid (PFOA) is a member of a family of perfluorinated chemicals that have a variety of applications. PFOA persists in the environment and is found in wildlife and humans. In mice, PFOA is developmentally toxic producing mortality, delayed eye opening, growth deficits, and altered pubertal maturation. PFOA activates peroxisome proliferators-activated receptor-alpha (PPARalpha), a pathway critical to the mode of induction of liver tumors in rodents. The present study uses 129S1/SvlmJ wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
143
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(156 citation statements)
references
References 38 publications
10
143
2
Order By: Relevance
“…The NOEL for developmental toxicity of PFHxA salt in mice from the study is 35 mg/kg/day. The adverse effects noted on pup bodyweight, postnatal survival, and attainment of developmental landmarks are consistent with effects noted in mice after PFOA administration; however, the LOELs for these effects in the study conducted with PFHxA are at least two orders of magnitude greater than the respective LOELs for PFOA in mice, the most sensitive species [49], of 0.6 mg/kg/day and 1 mg/kg/day, respectively, emphasizing the decreased potency of the C6 compound compared with PFOA.…”
Section: Systemic and Reproductive Toxicologysupporting
confidence: 68%
“…The NOEL for developmental toxicity of PFHxA salt in mice from the study is 35 mg/kg/day. The adverse effects noted on pup bodyweight, postnatal survival, and attainment of developmental landmarks are consistent with effects noted in mice after PFOA administration; however, the LOELs for these effects in the study conducted with PFHxA are at least two orders of magnitude greater than the respective LOELs for PFOA in mice, the most sensitive species [49], of 0.6 mg/kg/day and 1 mg/kg/day, respectively, emphasizing the decreased potency of the C6 compound compared with PFOA.…”
Section: Systemic and Reproductive Toxicologysupporting
confidence: 68%
“…Several studies have examined the toxicity of different PFC in many aquatic and other animals (24,32,33). These studies have confirmed that exposure during particular developmental stages or under certain nutritional conditions produced adverse effects on neonates (34,35).…”
Section: Discussionmentioning
confidence: 95%
“…Severe heart abnormalities such as atrial septal defects have been reported in association with the NKX2.5 mutation and downregulation. PFHxA and PFHpA treatments reduced the expression of NKX2.5 mRNA, which is critical for vasculogenesis and angiogenesis (32). Thus, PFCs may cause improper septum formation and impair cardiac function by downregulating the expression of NKX2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated developmental effects of the other PFAAs, which were observed even at doses which produced no maternal toxicity (ATSDR, 2009;Butenhoff et al, 2004;Case et al, 2001;Das et al, 2008;Harris and Birnbaum, 1989;Lau et al, 2006Lau et al, , 2003Luebker et al, 2005aLuebker et al, , 2005bThibodeaux et al, 2003). Abbott et al (2007) reported an increase in the incidence of full litter loss, reduction of neonatal survival and body weight gain and delayed eye opening in mice given PFOA during days 1-17 of gestation at 0.6 mg/kg/day and above. Interestingly, such developmental effects were not detected in PPARα knockout mice given the same dose.…”
Section: Discussionmentioning
confidence: 95%